The Evaluation of Hepatocellular Carcinoma with Biphasic Contrast Enhanced Spiral CT Scan - Afrin, Rawnak; Sarker, Snigdha; Mostofa, ABM Golam; Hossain, Mohammad Sazzad; Nahid, Sajida; Saiham, Shantono; Alom, Md Zahangir (Sir Salimullah Medical College Journal, 2022)
Background: Hepatocellular Carcinoma (HCC) is the most common malignant neoplasm of the liver worldwide. Liver cancer ranks third among all cancer deaths in Bangladesh as the clinical presentation is non-specific, the modern imaging modalities can play an important role in the diagnosis of HCC and the radiologist is often the first to suggest the correct diagnosis. With the advent of multi-detector spiral CT, detection and characterization of HCC has markedly improved. Multi-detector spiral CT with its increased spatial and temporal resolution allows multiple perfusion phases of liver to be acquired.Multi-detector biphasic spiral CT techniques have been increasingly promising with respect to accurate preoperative diagnosis and assessment of the extent of HCC. This study was carried out to evaluate the role of biphasic contrast-enhanced spiral CT including Hepatic Arterial Phase (HAP) imaging with Portal Venous Phase (PVP) imaging, in the detection and characterization of HCC. Methods: The study included 35 patients (M=31, F=4) with histopathologically proven HCC. Age range was between 21-75 years (mean=51) by following consecutive patients in whom HCC was diagnosed or suspected either by raised serum a (alpha)-fetoprotein level or byultrasound imaging. Results: Biphasic contrast-enhanced examination in these 35 patients could reveal a total of 65 lesions, out of which 48% were unifocal and 46% were multifocal HCCs. On HAP imaging 92% lesions were detected. (hyper attenuating = 56, hypo attenuating = 4) while on PVP imaging delectability was only 51% (hyper attenuating=2, hypo attenuating=30). Hence delectability was significantly superior in HAP as compared to PVP imaging (p <0.0001, 95% CI 25.2-54.7). In 49% tumor was visible only on HAP images. Venous invasion was present in 11 patients (31%). Conclusion: Biphasic contrast enhanced spiral CT is a useful method in detection and characterization of HCC. Sir Salimullah Med Coll J 2022; 30: 61-66